A muscle-like magnetorheological actuator based on bidisperse magnetic particles enhanced flexible alginate-gelatin sponges. (2nd December 2019) - Fu, Yu; Yao, Jianjun; Zhao, Honghao; Zhao, Gang; Wan, Zhenshuai; Guo, Ruizhi
Abstract: A novel muscle-like magnetorheological actuator (MMRA) was composed of magnetic field generator and magnetostrictive component. Herein, the magnetostrictive component with high flexibility and elasticity was constructed by embedding micron carbonyl iron particles and Fe3 O4 nanoparticles wrapped with MWCNTs into the alginate-gelatin (AL-GE) sponge matrix through a freeze-drying method for the first time. The structural characterization, rheological properties and actuation performance of MMRA with various magnetic AL-GE sponges were investigated. And they were significantly influenced by the mass ratio of AL-GE and the mass fraction of bidisperse magnetic particles (BMPs). The results showed that the relative MR effect and loss factor under 1 T of sample AL1 -GE4 -30 are 324.11% and 0.18, and its maximum deformation is 3.46 mm at 200 mT of magnetic flux density, exhibiting superior flexibility and enhanced magneto-induced performance compared with other magnetic AL-GE sponge matrix. In addition, a possible mechanism was proposed to explain the magneto-controllable performance for the MMRA. It was found that the actuation behaviors were attributed to the uniform distribution of BMPs in the homogenous network structure of sponge matrix.